O lugar do Édipo na psicanálise: reverberações de uma estrutura - Machado, Alan Oliveira (2019)
In this thesis we aim at discussing the ascertainment that Edipus complex remains in the psychoanalisis until the last Freud’s writings. We state that, during all Freud’s elaboration, he emphasizes a psychic structure in which a dialect of desire is kept. We undertake our readings from the Lacanian point of view, taking the stated structure as a structure of language. Although not so directly revealed in Freud's work, it is linked, from the initial texts, to the understanding of the psychic apparatus as a language apparatus, since his The interpretation of dreams, a book that was the starting point of psychoanalysis. We will also discuss how it is developed in his early studies on aphasias and in later approaches such as that carried out in the Wunderblok approach. From Freud’s and Lacan’s theories, we observe that this structure has a dialect core: the phalus, the father, the name-of-the-father and the paternal metaphor, going through Lacan's enunciation on his return to the Freudian text, supported by the linguistic studies of Saussure, Jakobson and by the elaborations achieved by Lévi-Strauss on the structure of the myths. We see Lacan as a freudian one without ignoring the age Lacan elaborated his thoughts, this permited him to think and to keep the unconscious as language. Since Freud the language apparatus was in his theories, but it did not find scientific support in the linguistic field to be developed. We emphasize, therefore, our understanding of Lacan as a Freudian one, but without disregarding its origin in a situation that is no longer Freud’s, which will unleash its importance as a structural unconscious as a language. Thus, we can understant that the Freudian development over a long period of time, although, in its time, no theoretical support has been found in the science of the language.